Polyarylene sulfide resin composition

By combining a fibrous inorganic filler with a specific diameter ratio and an alkoxysilane compound, the polyarylene sulfide resin composition significantly enhances bending and impact strength, addressing the limitations of existing technologies.

JP7606056B2Active Publication Date: 2024-12-24DAICEL CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024544270
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-09-01
Filing Date
2023-08-29
Publication Date
2024-12-24
Estimated Expiration
2043-08-29

AI Technical Summary

Technical Problem

Existing polyarylene sulfide resin compositions do not adequately enhance bending strength and impact strength, despite their excellent heat resistance and mechanical properties.

Method used

Incorporating a fibrous inorganic filler with a specific diameter ratio of 3.0 or more and an alkoxysilane compound into the polyarylene sulfide resin, with a cooling crystallization temperature of 215°C or higher, to create a resin composition that synergistically improves bending and impact strength.

Benefits of technology

The resulting resin composition achieves a molded article with enhanced bending strength and impact strength, surpassing conventional products, making it suitable for various applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606056000001
    Figure 0007606056000001
Patent Text Reader

Abstract

Provided is a polyarylene sulfide resin composition that can give molded articles that exhibit an excellent bending strength and an excellent impact strength. The polyarylene sulfide resin composition comprises a polyarylene sulfide resin (A); a fibrous inorganic filler (B) that has an aspect ratio of at least 3.0, wherein this aspect ratio is the ratio between the major axis and minor axis of a cross section perpendicular to the longitudinal direction; and an alkoxysilane compound (C). The cooling crystallization temperature (Tc) of the polyarylene sulfide resin (A) is at least 215°C; the content of the fibrous inorganic filler (B) that has an aspect ratio of at least 3.0, wherein this aspect ratio is the ratio between the major axis and minor axis of a cross section perpendicular to the longitudinal direction, is 55 to 180 parts by mass per 100 parts by mass of the polyarylene sulfide resin (A); and the content of the alkoxysilane compound (C) is 0.5 to 10 parts by mass per 100 parts by mass of the polyarylene sulfide resin (A).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyarylene sulfide resin composition. [Background technology]

[0002] Polyarylene sulfide resins, typified by polyphenylene sulfide resins, are widely used as materials for electrical and electronic equipment parts, automobile parts, chemical equipment parts, etc. because of their excellent heat resistance, mechanical properties, chemical resistance, dimensional stability, and flame retardancy.

[0003] In order to increase the mechanical strength of polyarylene sulfide resin molded products, techniques such as blending glass fibers having a flat cross-sectional shape (e.g., Patent Document 1) and blending fillers whose surfaces have been treated with alkoxysilane compounds (e.g., Patent Document 2) have been investigated.

[0004] [Patent Document 1] International Publication No. 2021 / 157162 [Patent Document 2] Japanese Patent Application Publication No. 08-012886 Summary of the Invention

[0005] An object of the present invention is to provide a polyarylene sulfide resin composition capable of giving a molded article having excellent flexural strength and impact strength.

[0006] The present invention has the following aspects. [1] A fiber-like inorganic filler comprising: (A) a polyarylene sulfide resin; (B) a fibrous inorganic filler having a difference-in-diameter ratio, which is the ratio of the major axis to the minor axis in a cross section perpendicular to the longitudinal direction, of 3.0 or more; and (C) an alkoxysilane compound; the (A) polyarylene sulfide resin has a temperature-lowering crystallization temperature (Tc) of 215°C or higher, and the temperature-lowering crystallization temperature (Tc) is an exothermic peak temperature associated with crystallization observed when the (A) polyarylene sulfide resin is heated to 340°C by a differential scanning calorimeter, melted, and then cooled at a rate of 10°C / min; the content of the (B) fibrous inorganic filler having a diameter ratio, which is a ratio of the major axis to the minor axis of a cross section perpendicular to the longitudinal direction, of 3.0 or more, is 55 to 180 parts by mass relative to 100 parts by mass of the (A) polyarylene sulfide resin; A polyarylene sulfide resin composition, in which the content of the (C) alkoxysilane compound is 0.5 to 10 parts by mass per 100 parts by mass of the (A) polyarylene sulfide resin. [2] The polyarylene sulfide resin composition according to [1], wherein the (C) alkoxysilane compound contains one or more alkoxysilane compounds having one or more selected from an epoxy group, an amino group, a vinyl group, a (meth)acrylic group, an isocyanate group, and a mercapto group. [3] The polyarylene sulfide resin composition according to [1] or [2], wherein the (B) fibrous inorganic filler having a difference-in-diameter ratio, which is the ratio of the long axis to the short axis in a cross section perpendicular to the longitudinal direction, of 3.0 or more contains glass fiber.

[0007] According to the present invention, it is possible to provide a polyarylene sulfide resin composition which can give a molded article having excellent bending strength and impact strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, one embodiment of the present invention will be described in detail, but the scope of the present invention is not limited to the embodiment described here, and various modifications can be made without departing from the spirit of the present invention. In addition, when multiple upper and lower limit values ​​are described for a specific parameter, any upper and lower limit values ​​among these upper and lower limit values ​​can be combined to form a suitable numerical range. The expression "X to Y" indicating a numerical range means "X or more and Y or less". When a specific description described for one embodiment is also applicable to other embodiments, the description may be omitted in other embodiments.

[0009] [Polyarylene sulfide resin composition] The polyarylene sulfide resin composition according to the present embodiment (hereinafter, also simply referred to as the "resin composition") comprises (A) a polyarylene sulfide resin, (B) a fibrous inorganic filler having a difference diameter ratio, which is the ratio of the major axis to the minor axis in a cross section perpendicular to the longitudinal direction, of 3.0 or more, and (C) an alkoxysilane compound, and the polyarylene sulfide resin (A) has a temperature-lowering crystallization temperature (Tc) of 215°C or more, provided that the temperature-lowering crystallization temperature (Tc) is determined by differential scanning calorimetry of the polyarylene sulfide resin (A). The exothermic peak temperature associated with crystallization observed when the resin is heated to 340°C by a calorimeter, melted, and then cooled at a rate of 10°C / min, the content of (B) a fibrous inorganic filler having a difference diameter ratio, which is the ratio of the major axis to the minor axis of a cross section perpendicular to the longitudinal direction, of 3.0 or more is 55 to 180 parts by mass relative to 100 parts by mass of (A) polyarylene sulfide resin, and the content of (C) an alkoxysilane compound is 0.5 to 10 parts by mass relative to 100 parts by mass of (A) polyarylene sulfide resin. The resin composition according to this embodiment can provide a molded product having excellent bending strength and impact strength.

[0010] <(A) Polyarylene sulfide resin> The (A) polyarylene sulfide resin is a resin having a repeating unit represented by the following general formula (I). -(Ar-S)- (I) (wherein Ar represents an arylene group).

[0011] The arylene group is not particularly limited, and examples thereof include p-phenylene group, m-phenylene group, o-phenylene group, substituted phenylene group, p,p'-diphenylene sulfone group, p,p'-biphenylene group, p,p'-diphenylene ether group, p,p'-diphenylene carbonyl group, naphthalene group, etc. The (A) polyarylene sulfide resin can be a homopolymer using the same repeating unit among the repeating units represented by the above general formula (I), or a copolymer containing different repeating units depending on the application.

[0012] As the homopolymer, one having a p-phenylene group as an arylene group and a p-phenylene sulfide group as a repeating unit is preferable. This is because a homopolymer having a p-phenylene sulfide group as a repeating unit has extremely high heat resistance, and exhibits high strength, high rigidity, and high dimensional stability over a wide temperature range. By using such a homopolymer, a molded product with very excellent physical properties can be obtained.

[0013] As the copolymer, a combination of two or more different arylene sulfide groups among the above-mentioned arylene group-containing arylene sulfide groups can be used. Among these, a combination containing a p-phenylene sulfide group and an m-phenylene sulfide group is preferred from the viewpoint of obtaining a molded product having high physical properties such as heat resistance, moldability, and mechanical properties. A polymer containing 70 mol % or more of p-phenylene sulfide groups is more preferred, and a polymer containing 80 mol % or more is even more preferred. The (A) polyarylene sulfide resin having phenylene sulfide groups is a polyphenylene sulfide resin (PPS resin).

[0014] Generally, polyarylene sulfide resins are known to have a substantially linear molecular structure having no branched or crosslinked structure, and a structure having a branched or crosslinked structure, depending on the production method, and either type may be used as the (A) polyarylene sulfide resin.

[0015] (A) Polyarylene sulfide resin at 310°C and a shear rate of 1200 sec -1 From the viewpoint of improving moldability and toughness, the melt viscosity measured by is preferably from 3 to 250 Pa·s, more preferably from 5 to 150 Pa·s, and further preferably from 8 to 80 Pa·s.

[0016] The cooling crystallization temperature (Tc) of the (A) polyarylene sulfide resin is 215° C. or higher, preferably exceeds 215° C., more preferably is 216° C. or higher, further preferably is 220° C. or higher, and particularly preferably is 230° C. or higher. Surprisingly, when the (A) polyarylene sulfide resin has a cooling crystallization temperature (Tc) of 215° C. or higher, a synergistic effect can be sufficiently obtained by using the (A) polyarylene sulfide resin in combination with the (C) alkoxysilane compound described later, thereby increasing the bending strength and impact strength of the molded article. The upper limit of the cooling crystallization temperature (Tc) of the (A) polyarylene sulfide resin is preferably 260° C. or lower, more preferably 250° C. or lower, and particularly preferably 240° C. or lower. In one embodiment, the cooling-down crystallization temperature (Tc) of the polyarylene sulfide resin (A) may be 215 to 260° C., may be more than 215° C. and not more than 260° C., may be 216 to 250° C., or may be 216 to 240° C. In one embodiment, the cooling-down crystallization temperature (Tc) of the polyarylene sulfide resin (A) may be 219° C., or may be in a range with this as the upper limit or lower limit of the above numerical range.

[0017] The cooling crystallization temperature (Tc) is defined as the exothermic peak temperature associated with crystallization observed when the polyarylene sulfide resin (A) is heated to 340°C by a differential scanning calorimeter to melt it, and then cooled at a rate of 10°C / min. As a method for adjusting the crystallization temperature (Tc) of the (A) polyarylene sulfide resin by cooling to 215°C or higher, a washing treatment after polymerization is preferable because it is easy to process, but is not necessarily limited to this method. As a washing treatment method, for example, a method of washing the polymer after polymerization with an acidic aqueous solution of appropriate acidity can be mentioned. In this case, examples of the acid used as the acidic aqueous solution include inorganic acids such as hydrochloric acid, sulfuric acid, and ammonium chloride; saturated fatty acids such as acetic acid, formic acid, propionic acid, butyric acid, valeric acid, and caproic acid; unsaturated fatty acids such as acrylic acid, crotonic acid, and oleic acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, and salicylic acid; dicarboxylic acids such as oxalic acid, maleic acid, and fumaric acid; methanesulfonic acid and paratoluenesulfonic acid, among which hydrochloric acid, acetic acid, and ammonium chloride are preferred. In addition, before and after washing with the acidic aqueous solution, washing with an organic solvent such as acetone or water may be performed as necessary. For example, when the cooling-down crystallization temperature (Tc) is low, the cooling-down crystallization temperature (Tc) of the polyarylene sulfide resin (A) can be increased to 215°C or higher by subjecting the polyarylene sulfide resin (A) to a washing treatment with the above-mentioned compound (e.g., acetic acid, ammonium chloride, etc.).

[0018] The method for producing the polyarylene sulfide resin (A) is not particularly limited, and it can be produced by a conventionally known production method. For example, it can be produced by synthesizing a low molecular weight polyarylene sulfide resin, and then polymerizing it at high temperature in the presence of a known polymerization aid to increase the molecular weight. It may also be produced by blending a plurality of types of polyarylene sulfide resins. In this case, it can also be produced by combining polyarylene sulfide resins having different melt viscosities. When combining polyarylene sulfide resins having different melt viscosities, it is preferable that the melt viscosity of the resulting resin is within the above range. It is also possible to combine two or more polyarylene sulfide resins having different cooling crystallization temperatures (Tc) within a range in which the cooling crystallization temperature (Tc) of the resulting resin is 215°C or higher.

[0019] Polyarylene sulfide resins produced by general polymerization methods are usually washed several times with an organic solvent such as water or acetone to remove by-product impurities, etc. As described above, in one embodiment, the polyarylene sulfide resin (A) may then be further washed with acetic acid, ammonium chloride, etc.

[0020] In one embodiment, the content of the polyarylene sulfide resin (A) in the resin composition is preferably 30 mass% or more, more preferably 35 mass% or more. In one embodiment, the content of the polyarylene sulfide resin (A) in the resin composition may be 30 to 70 mass%, 30 to 65 mass%, or 35 to 60 mass%. In one embodiment, the thermoplastic resin contained in the resin composition may be preferably 80 mass% or more, more preferably 90 mass% or more of the polyarylene sulfide resin (A). In one embodiment, the thermoplastic resin contained in the resin composition may be composed only of the polyarylene sulfide resin (A).

[0021] <(B) Fibrous inorganic filler> The resin composition contains a fibrous inorganic filler (hereinafter also simply referred to as "(B) fibrous inorganic filler") having a diameter ratio (hereinafter also simply referred to as "diameter ratio"), which is the ratio of the long axis to the short axis of a cross section perpendicular to the longitudinal direction (long axis of cross section / short axis of cross section), of 3.0 or more.

[0022] The "long diameter of the cross section perpendicular to the longitudinal direction" is the longest linear distance in the cross section perpendicular to the longitudinal direction of the fiber, and the "short diameter of the cross section perpendicular to the longitudinal direction" is the longest linear distance perpendicular to the long diameter in the cross section. The diameter ratio refers to the diameter ratio of the initial shape (shape before melt kneading). The diameter ratio can be calculated using a scanning electron microscope and image processing software, and is the arithmetic average value measured for 10 (B) fibrous inorganic fillers. The diameter ratio may also be the manufacturer's value (a value published by the manufacturer in a catalog, etc.).

[0023] Generally, as indicators of the mechanical strength of a resin molded product, there are tensile strength indicating the strength when a tensile force is applied to the molded product, bending strength indicating the strength when a bending load is applied to the molded product, and impact strength indicating the strength when an impact is applied to the molded product. Since the direction and method of applying force are different for each of these indicators, if one indicator is excellent, the other indicators are not necessarily excellent. For example, even if the tensile strength is excellent, the bending strength is not necessarily excellent. The resin composition according to this embodiment can provide a molded product having excellent mechanical strength, particularly bending strength and impact strength, by using (A) a polyarylene sulfide resin in combination with (B) a fibrous inorganic filler having a predetermined diameter ratio and (C) an alkoxysilane compound described later in a predetermined amount.

[0024] The diameter ratio of the (B) fibrous inorganic filler is 3.0 or more, preferably 3.5 or more, and more preferably 3.8 or more. The upper limit of the diameter ratio is 10.0 or less, preferably 8.0 or less, and more preferably 6.0 or less. In one embodiment, the diameter ratio of the (B) fibrous inorganic filler may be 3.0 to 10.0, 3.5 to 8.0, or 3.8 to 6.0. In one embodiment, the diameter ratio of the (B) fibrous inorganic filler may be 4.0, or may be the upper limit or lower limit of the above-mentioned numerical range.

[0025] (B) Examples of fibrous inorganic fillers include fibrous inorganic fillers whose cross-sectional shape perpendicular to the longitudinal direction of the fiber is oval, semicircular, cocoon-shaped (an oval shape with a portion of the longitudinal direction recessed inward), rectangular, or similar shapes.

[0026] The major axis of the cross section perpendicular to the longitudinal direction of the (B) fibrous inorganic filler is preferably 10 to 40 μm, and more preferably 20 to 30 μm. The minor axis of the cross section perpendicular to the longitudinal direction of the (B) fibrous inorganic filler is preferably 1 to 20 μm, and more preferably 3 to 10 μm. The major axis and minor axis of the cross section perpendicular to the longitudinal direction can be calculated using a scanning electron microscope and image processing software, and are the arithmetic average values ​​measured for 10 pieces of (B) fibrous inorganic filler. In addition, the major axis and minor axis of the cross section perpendicular to the longitudinal direction can be the manufacturer's values ​​(values ​​published by the manufacturer in the catalog, etc.).

[0027] From the viewpoint of further increasing the bending strength and impact strength of the molded product, the average fiber length of the (B) fibrous inorganic filler is preferably 0.01 to 3.5 mm, more preferably 0.05 to 3.5 mm, even more preferably 0.1 to 3.5 mm, and particularly preferably 0.5 to 3 mm, as the average fiber length (cut length) before melt-kneading in the resin composition. The average fiber length can be calculated using a scanning electron microscope and image processing software, and is the arithmetic average value measured for 1,000 pieces of (B) fibrous inorganic filler. The average fiber length can also be the manufacturer's value (a value published by the manufacturer in a catalog, etc.).

[0028] The average fiber length of the (B) fibrous inorganic filler in the molded article is preferably 50 to 1000 μm, more preferably 100 to 900 μm, from the viewpoint of further increasing the bending strength and impact strength of the molded article. The average fiber length of the (B) fibrous inorganic filler in the molded article can be calculated by dispersing 3 mg of the residue obtained by heating the molded article at 600° C. for 3 to 5 hours and incinerating it in water in a 5% polyethylene glycol aqueous solution, stirring thoroughly, and then transferring 10 mL to a petri dish and using an image measuring device. The arithmetic average value measured for 1000 (B) fibrous inorganic fillers is used.

[0029] (B) The cross-sectional area of ​​the fibrous inorganic filler is set to 1×10 for ease of production. -5 ~1×10 -3 mm 2 Preferably, the concentration is 1×10 -4 ~5×10 -4 mm 2It is more preferable that the cross-sectional area is π. The "cross-sectional area" can be calculated by dividing the longest straight-line distance of the cross-section of the (B) fibrous inorganic filler measured using a scanning electron microscope and image processing software by the longest straight-line distance being the longest straight-line distance and the shortest straight-line distance being the shortest straight-line distance, by dividing the longest straight-line distance by 2 and multiplying the result by π, which is the circular constant. The cross-sectional area is the arithmetic average value measured for 10 (B) fibrous inorganic fillers.

[0030] Examples of the material of the (B) fibrous inorganic filler include mineral fibers such as glass fiber, carbon fiber, zinc oxide fiber, titanium oxide fiber, wollastonite, silica fiber, silica-alumina fiber, zirconia fiber, boron nitride fiber, silicon nitride fiber, boron fiber, potassium titanate fiber, etc., and metal fibrous materials such as stainless steel fiber, aluminum fiber, titanium fiber, copper fiber, brass fiber, etc., and it is preferable to use one or more selected from these. Among them, it is more preferable to include glass fiber. In addition, hollow fibers can be used as the (B) fibrous inorganic filler for the purpose of reducing the specific gravity of the resin composition, etc.

[0031] The (B) fibrous inorganic filler may be surface-treated with various surface treatment agents such as commonly known epoxy compounds, isocyanate compounds, silane compounds, titanate compounds, fatty acids, etc. The surface treatment can improve adhesion to the (A) polyarylene sulfide resin. The surface treatment agent may be applied to the (B) fibrous inorganic filler in advance before the material is prepared to perform surface treatment or convergence treatment, or may be added simultaneously when the material is prepared.

[0032] The content of the (B) fibrous inorganic filler is 55 to 180 parts by mass, preferably 58 to 170 parts by mass, more preferably 60 to 160 parts by mass, and even more preferably 65 to 155 parts by mass, relative to 100 parts by mass of the (A) polyarylene sulfide-based resin. By using the (B) fibrous inorganic filler in an amount of 55 to 180 parts by mass relative to 100 parts by mass of the (A) polyarylene sulfide-based resin, a synergistic effect due to the combined use with the (C) alkoxysilane compound described later can be sufficiently obtained, and the bending strength and impact strength of the molded article can be increased. In one embodiment, the content of the fibrous inorganic filler (B) may be 68 to 153 parts by mass relative to 100 parts by mass of the polyarylene sulfide resin (A). In one embodiment, the content of the fibrous inorganic filler (B) may be 68 parts by mass, 101 parts by mass, 102 parts by mass, or 153 parts by mass relative to 100 parts by mass of the polyarylene sulfide resin (A), or may be within a range with these as upper or lower limits.

[0033] The content of the fibrous inorganic filler (B) in the resin composition is preferably 35 to 65 mass%, more preferably 36 to 64 mass%. In one embodiment, the content of the fibrous inorganic filler (B) in the resin composition may be 40 to 61 mass%.

[0034] As described later, the resin composition may contain other inorganic fillers other than the (B) fibrous inorganic filler, if necessary, but the content of the (B) fibrous inorganic filler in the total inorganic fillers is preferably 50 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more. In one embodiment, the inorganic filler may be composed of the (B) fibrous inorganic filler.

[0035] <Other inorganic fillers> The resin composition may contain, in addition to the (B) fibrous inorganic filler, other inorganic fillers as necessary. Examples of the other inorganic fillers include fibrous inorganic fillers other than the (B) fibrous inorganic filler and non-fibrous inorganic fillers.

[0036] Examples of fibrous inorganic fillers other than (B) fibrous inorganic fillers include fibrous fillers whose diameter ratio, which is the ratio of the long diameter to the short diameter of a cross section perpendicular to the longitudinal direction, is less than 3.0, less than 2.0, or 1.5 or less. Examples of fibrous inorganic fillers other than (B) fibrous inorganic fillers include, for example, fibrous inorganic fillers whose cross section perpendicular to the longitudinal direction of the fiber is round or square. The material of the fibrous inorganic filler other than (B) fibrous inorganic filler is not limited, and may include the fibrous fillers exemplified in the above-mentioned (B) fibrous inorganic filler, and may include one or more selected from them. The material of (B) fibrous inorganic filler and the fibrous inorganic filler other than (B) fibrous inorganic filler may be the same or different. The average fiber length and average fiber diameter of the other fibrous inorganic filler are not limited.

[0037] Examples of the non-fibrous inorganic filler include powdered granular inorganic fillers and plate-like inorganic fillers. Examples of the powdered inorganic filler include carbon black, silica, quartz powder, glass beads, glass powder, talc (granular), silicates such as calcium silicate, aluminum silicate, and diatomaceous earth, metal oxides such as iron oxide, titanium oxide, zinc oxide, and alumina, metal carbonates such as calcium carbonate and magnesium carbonate, metal sulfates such as calcium sulfate and barium sulfate, and silicon carbide, silicon nitride, boron nitride, and various metal powders, and may contain one or more selected from these. Examples of the plate-like inorganic filler include glass flakes, talc (plate-like), mica, kaolin, clay, alumina, and various metal foils, and may contain one or more selected from these. The average particle size (D50) of the non-fibrous inorganic filler is not limited and may be, for example, 0.1 to 100 μm.

[0038] The content of the other inorganic filler is not limited, and can be, for example, 0 to 50 parts by mass, and can also be less than 40 parts by mass, relative to 100 parts by mass of the (A) polyarylene sulfide resin. In one embodiment, the amount of the other inorganic filler is preferably small. In one embodiment, the content of the fibrous filler having a diameter ratio, which is the ratio of the major axis to the minor axis in a cross section perpendicular to the longitudinal direction, of less than 3.0 is preferably less than 1 part by mass, more preferably less than 0.5 parts by mass, and even more preferably less than 0.1 parts by mass, relative to 100 parts by mass of the (A) polyarylene sulfide resin. In one embodiment, the composition may be configured so as not to contain any fibrous filler having a diameter ratio, which is the ratio of the major axis to the minor axis in a cross section perpendicular to the longitudinal direction, of less than 3.0.

[0039] <(C) Alkoxysilane Compound> The resin composition contains an alkoxysilane compound (C). The alkoxysilane compound (C) preferably contains one or more alkoxysilane compounds having one or more groups selected from an epoxy group, an amino group, a vinyl group, a (meth)acrylic group, an isocyanate group, and a mercapto group.

[0040] In one embodiment, the alkoxysilane compound (C) is preferably represented by the following formula (II): R 1 n Si(OR 2 ) 4-n (II) In formula (II), R 1 is an alkyl group having 1 to 18 carbon atoms (preferably 1 to 10) and having an epoxy group, an amino group, a vinyl group, a (meth)acrylic group, an isocyanate group, or a mercapto group, and R 2 is an alkyl group having 1 to 4 carbon atoms, and n is an integer of 1 to 3.

[0041] Examples of the (C) alkoxysilane compound include alkoxysilanes such as epoxyalkoxysilane, aminoalkoxysilane, vinylalkoxysilane, (meth)acrylicalkoxysilane, isocyanatealkoxysilane, and mercaptoalkoxysilane, and it is preferable to contain one or more of these. The number of carbon atoms in the alkoxy group is preferably 1 to 10, and particularly preferably 1 to 4. The (C) alkoxysilane compound can contain one or more of them.

[0042] Examples of epoxyalkoxysilanes include γ-glycidoxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and γ-glycidoxypropyltriethoxysilane.

[0043] Examples of aminoalkoxysilanes include γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-diallylaminopropyltrimethoxysilane, and γ-diallylaminopropyltriethoxysilane.

[0044] Examples of vinylalkoxysilanes include vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltris(β-methoxyethoxy)silane.

[0045] Examples of (meth)acrylalkoxysilanes include γ-acryloxypropyltriethoxysilane, γ-acryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, and γ-methacryloxypropylmethyldiethoxysilane.

[0046] Examples of the isocyanate alkoxysilane include γ-isocyanate propyl triethoxysilane and γ-isocyanate propyl trimethoxysilane.

[0047] Examples of mercaptoalkoxysilanes include γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane.

[0048] Among these, it is more preferable that the compound contains one or more selected from epoxyalkoxysilanes and aminoalkoxysilanes, and it is particularly preferable that the compound contains γ-aminopropyltriethoxysilane.

[0049] The content of the (C) alkoxysilane compound is 0.5 to 10 parts by mass, preferably 0.6 to 8 parts by mass, and more preferably 0.7 to 4.5 parts by mass, relative to 100 parts by mass of the (A) polyarylene sulfide resin. By using the (C) alkoxysilane compound in an amount of 0.5 to 10 parts by mass relative to 100 parts by mass of the (A) polyarylene sulfide resin, a synergistic effect due to the combined use with the (B) fibrous inorganic filler can be sufficiently obtained, and the bending strength and impact strength of the molded article can be increased. In one embodiment, the content of the (C) alkoxysilane compound may be 0.5 parts by mass, 1.0 parts by mass, 1.2 parts by mass, or 1.5 parts by mass relative to 100 parts by mass of the (A) polyarylene sulfide resin, or may be within a range defined by these upper and lower limits.

[0050] As described above, (B) fibrous inorganic filler can be surface-treated with silane-based compounds and the like. In one embodiment, when (B) fibrous inorganic filler is surface-treated with alkoxysilane compounds, the content of (C) alkoxysilane compounds can include the content of alkoxysilane compounds derived from surface treatment agents. Even in this case, the content of (C) alkoxysilane compounds is preferably within the above range.

[0051] (Other additives, etc.) The resin composition may contain known additives generally added to thermoplastic resins and thermosetting resins according to the required performance in order to impart desired properties according to the purpose, within a range that does not impair the effects of the present invention. Examples of additives include burr inhibitors, release agents, lubricants, plasticizers, flame retardants, colorants such as dyes and pigments, crystallization accelerators, crystal nucleating agents, various antioxidants, heat stabilizers, weather resistance stabilizers, and corrosion inhibitors. Examples of release agents include polyethylene wax, fatty acid esters, fatty acid amides, and the like. Examples of crystal nucleating agents include boron nitride, talc, kaolin, carbon black, and carbon nanotubes. Examples of corrosion inhibitors include zinc oxide and zinc carbonate. The content of the above additives can be 5% by mass or less in the entire resin composition.

[0052] In addition, in addition to the above components, the resin composition may also be supplementarily used in small amounts with other thermoplastic resin components depending on the purpose. The other thermoplastic resin used here may be any resin that is stable at high temperatures. For example, aromatic polyesters such as polyethylene terephthalate and polybutylene terephthalate, which are made of aromatic dicarboxylic acid and diol, or oxycarboxylic acid, polyamide, polycarbonate, ABS, polyphenylene oxide, polyalkyl acrylate, polysulfone, polyethersulfone, polyetherimide, polyether ketone, fluororesin, liquid crystal polymer, cyclic olefin copolymer, etc. may be mentioned. Two or more of these thermoplastic resins may also be mixed and used. The content of the other thermoplastic resin components may be, for example, 20 mass% or less in the total resin composition.

[0053] (Method for producing polyarylene sulfide resin composition) The method for producing the resin composition is not particularly limited, and the resin composition can be produced by melt-kneading the above-mentioned components by a known method. For example, the resin composition can be produced by mixing the components, kneading and extruding the components with an extruder to prepare pellets, by first preparing pellets with different compositions, mixing the pellets in a predetermined amount and subjecting them to molding to obtain a molded product with the desired composition after molding, or by directly charging one or more of the components into a molding machine.

[0054] The resin composition preferably has a tensile strength (TS) of 195 MPa or more, and if it is 195 MPa or more, it can be said that the resin composition has a tensile strength equal to or greater than that of conventional resins. The resin composition according to this embodiment can provide a molded product having a tensile strength equal to or greater than that of conventional resins. The tensile strength (TS) is measured in accordance with ISO527-1,2 using a type A test piece (width 10 mm, thickness 4 mmt) according to ISO3167:93, which is prepared by injection molding at a cylinder temperature of 320°C and a mold temperature of 150°C after drying pellets of the resin composition at 140°C for 3 hours.

[0055] The resin composition has a flexural strength (FS) of 290 MPa or more, and more preferably 300 MPa or more. The resin composition according to the present embodiment can provide a molded article having improved flexural strength compared to conventional products. The flexural strength (FS) is measured in accordance with ISO178 using a test piece (width 10 mm, thickness 4 mmt) according to ISO316, which is prepared by injection molding at a cylinder temperature of 320°C and a mold temperature of 150°C after drying pellets of the resin composition at 140°C for 3 hours.

[0056] The resin composition preferably has a molded article having a Charpy impact strength (notched) of 11.0 kJ / m 2 More preferably, it is 11.5 kJ / m or more. 2 More preferably, it is 15.0 kJ / m 2That is all. According to the resin composition of this embodiment, it is possible to obtain a molded product having improved Charpy impact strength compared to the conventional one. The Charpy impact strength is a value measured in accordance with ISO179-1 using a test piece (width 10 mm, thickness 4 mmt, notched) according to ISO316, which is prepared by injection molding after drying pellets of the resin composition at 140°C for 3 hours and at a cylinder temperature of 320°C and a mold temperature of 150°C.

[0057] (Application) The resin composition of the present embodiment can give molded articles having excellent flexural strength and impact strength, and can be used in a variety of applications, such as electrical and electronic equipment parts, automobile parts, and chemical equipment parts. EXAMPLES

[0058] The present invention will be described in more detail below with reference to examples, but the interpretation of the present invention is not limited to these examples.

[0059] [Examples 1 to 7, Comparative Examples 1 to 11] Using the materials shown below, a polyarylene sulfide resin, a fibrous inorganic filler, and an alkoxysilane compound were dry-blended in the composition and content ratio shown in Table 1. This was fed into a twin-screw extruder with a cylinder temperature of 320°C (glass fiber was added separately from the side feed part of the extruder) and melt-kneaded to obtain resin composition pellets of the examples and comparative examples.

[0060] (Polyarylene sulfide resin) PPS-1: Polyphenylene sulfide resin, "Fortron KPS" manufactured by Kureha Corporation (melt viscosity: 30 Pa·s (shear rate: 1200 sec -1 , 310℃), Tc: 219℃) PPS-2: Polyphenylene sulfide resin (Tc: 183℃) synthesized by the following method

[0061] (Method of synthesis of PPS-2) A 20 L autoclave was charged with 5700 g of NMP and purged with nitrogen gas. The mixture was heated to 100°C over about 1 hour while stirring at a stirrer speed of 250 rpm. After reaching 100°C, 1170 g of a 74.7 wt% NaOH aqueous solution, 1990 g of a sulfur source aqueous solution (21.8 mol of NaSH and Na 2 The temperature was gradually raised to 200° C. over about 2 hours, and 945 g of water, 1590 g of NMP, and 0.31 mol of hydrogen sulfide were discharged out of the system. After the dehydration step, the mixture was cooled to 170° C., and 3459 g of p-DCB, 2800 g of NMP, 133 g of water, and 23 g of NaOH with a concentration of 97% by weight were added, and the temperature inside the vessel became 130° C. Subsequently, the mixture was heated to 180° C. over 30 minutes while stirring at a stirrer speed of 250 rpm, and then heated from 180° C. to 220° C. over 60 minutes. After reacting at that temperature for 60 minutes, the mixture was heated to 230° C. over 30 minutes, and reacted at 230° C. for 90 minutes to perform pre-stage polymerization. Immediately after the completion of the first-stage polymerization, the rotation speed of the stirrer was increased to 400 rpm, and 340 g of water was injected. After the water injection, the temperature was raised to 260°C in 1 hour, and the reaction was continued at that temperature for 5 hours to carry out the second-stage polymerization. After the completion of the second-stage polymerization, the reaction mixture was cooled to about room temperature, and the contents were sieved through a 100 mesh screen to obtain a granular polymer. The granular polymer was then washed three times with acetone and five times with water to obtain a washed granular polymer. The granular polymer was dried at 105°C for 13 hours. The granular polymer thus obtained had a melt viscosity (shear rate: 1200 sec -1 , 310℃) was 30 Pa·s. This procedure was repeated five times to obtain the required amount of polymer (PPS-2).

[0062] (Melt viscosity measurement of PPS resin) The melt viscosity of the PPS resin was measured as follows: using a Capillograph manufactured by Toyo Seiki Seisakusho Co., Ltd., a flat die of 1 mmφ×20 mmL was used as a capillary, the barrel temperature was 310° C., and the shear rate was 1200 sec -1 The melt viscosity at 100° C. was measured.

[0063] (Method of measuring Tc) The Tc of the above PPS resin was measured as follows. Approximately 5 mg of PPS resin was weighed out, and using a PerkinElmer DSC-8500 differential scanning calorimeter, the temperature was increased at a rate of 10°C / min, held at 340°C for 5 minutes, and then decreased at a rate of 10°C / min. The crystallization peak (exothermic peak) temperature was read from the obtained DSC chart to determine Tc.

[0064] (fibrous inorganic filler) GF1: Glass fiber, Nippon Electric Glass Co., Ltd., flat glass fiber ESC03T-760-FGF, cross section is oval, long diameter 28 μm, short diameter 7 μm, long diameter / short diameter ratio 4.0, average fiber length 3 mm GF2: Glass fiber, manufactured by Nitto Boseki Co., Ltd., irregular cross-section chopped strand CSG 3PA-830, cross section is oval, long diameter 28 μm, short diameter 7 μm, long diameter / short diameter ratio 4.0, average fiber length 3 mm Comparative GF: Glass fiber, manufactured by Nippon Electric Glass Co., Ltd., chopped strand ECS03T-717, cross section is approximately circular, long diameter 13 μm, short diameter 13 μm, long diameter / short diameter ratio 1.0, average fiber length 3 mm

[0065] (Alkoxysilane compounds) Alkoxysilane compound: γ-aminopropyltriethoxysilane, "KBE-903P" manufactured by Shin-Etsu Chemical Co., Ltd.

[0066] [measurement] (Tensile strength: TS) The resin composition pellets obtained in the examples and comparative examples were dried at 140°C for 3 hours, and then injection molded into A-type test pieces (width 10 mm, thickness 4 mmt) in accordance with ISO3167:93 at a molding cylinder temperature of 320°C and a mold temperature of 150°C. The tensile strength (MPa) of these test pieces was measured in accordance with ISO527-1,2. The results are shown in Table 1. A tensile strength of 195 MPa or more is evaluated as being equal to or greater than that of conventional products.

[0067] (Flexural strength: FS) The resin composition pellets obtained in the examples and comparative examples were dried at 140°C for 3 hours, and then injection molded to prepare test pieces (width 10 mm, thickness 4 mmt) in accordance with ISO316 at a molding cylinder temperature of 320°C and a mold temperature of 150°C. The test pieces were used to measure bending strength (MPa) in accordance with ISO178. The results are shown in Table 1. A bending strength of 290 MPa or more is evaluated as excellent bending strength.

[0068] (Charpy impact strength (notched)) The resin composition pellets obtained in the examples and comparative examples were dried at 140°C for 3 hours, and then injection molded into test pieces (width 10 mm, thickness 4 mmt) in accordance with ISO316 at a molding cylinder temperature of 320°C and a mold temperature of 150°C. Using these test pieces, the Charpy impact strength (notched) (kJ / m 2 The results are shown in Table 1. The Charpy impact strength was 11.0 kJ / m 2 If it is equal to or greater than this, the impact strength is evaluated as excellent.

[0069] [Table 1]

[0070] As shown in Table 1, the resin compositions of Examples 1 to 7 all had a bending strength of 290 MPa or more and a Charpy impact strength of 11.0 kJ / m 2 As a result, molded articles having excellent bending strength and impact strength can be obtained. In addition, the tensile strength is 195 MPa or more, and tensile strengths equal to or greater than those of conventional products can be achieved. In contrast, the resin compositions of Comparative Examples 1 to 6 use fibrous inorganic fillers with diameter ratios of less than 3.0, and even if they contain alkoxysilane compounds as in Comparative Examples 1 to 3, they are unable to achieve both excellent bending strength and impact strength. The resin composition of Comparative Example 7 had an alkoxysilane compound content of less than 0.5 parts by mass relative to 100 parts by mass of the polyarylene sulfide resin, and as a result had poor bending strength. In the resin composition of Comparative Example 8, the cooling crystallization temperature (Tc) of the polyarylene sulfide resin was less than 215° C., and the bending strength was poor. The resin compositions of Comparative Examples 9 to 11 did not contain an alkoxysilane compound, and even when a fibrous inorganic filler with a diameter difference ratio of 3.0 or more was used, the bending strength was poor. As shown in Comparative Examples 1, 7, 8, 10, and 11, even when the tensile strength is high, exceeding 195 MPa, the effect of improving the bending strength cannot be obtained. [Industrial Applicability]

[0071] Since the resin composition of the present embodiment can give molded articles having excellent bending strength and impact strength, it can be suitably used as a material for electric / electronic device parts, automobile parts, chemical device parts, and the like, and has industrial applicability.

Claims

1. (A) a thermoplastic resin containing a polyarylene sulfide resin (excluding polyetherimide resins); (B) a fibrous inorganic filler having a diameter ratio, which is the ratio of the major axis to the minor axis of a cross section perpendicular to the longitudinal direction, of 3.0 or more; and (C) an alkoxysilane compound, the (A) polyarylene sulfide resin has a temperature-lowering crystallization temperature (Tc) of 215° C. or higher, and the temperature-lowering crystallization temperature (Tc) is an exothermic peak temperature associated with crystallization observed when the (A) polyarylene sulfide resin is heated to 340° C. by a differential scanning calorimeter, melted, and then cooled at a rate of 10° C. / min; the content of the fibrous inorganic filler (B) having a diameter ratio, which is the ratio of the major axis to the minor axis of a cross section perpendicular to the longitudinal direction, of 3.0 or more, is 55 to 180 parts by mass relative to 100 parts by mass of the polyarylene sulfide resin (A); The polyarylene sulfide resin composition has a content of the alkoxysilane compound (C) of 0.6 to 4.5 parts by mass per 100 parts by mass of the polyarylene sulfide resin (A).

2. The polyarylene sulfide resin composition according to claim 1, wherein the alkoxysilane compound (C) comprises one or more alkoxysilane compounds having one or more groups selected from an epoxy group, an amino group, a vinyl group, a (meth)acrylic group, an isocyanate group, and a mercapto group.

3. 3. The polyarylene sulfide resin composition according to claim 1 or 2, wherein the (B) fibrous inorganic filler having a diameter ratio, which is a ratio of the major axis to the minor axis in a cross section perpendicular to the longitudinal direction, of 3.0 or more contains glass fiber.

Citation Information

Patent Citations

  • Polyarylene sulfide resin composition

    JP1996012886A

  • Polyarylene sulfide resin composition and injection molding

    JP2006328291A

  • Pressure-resistant container

    JP2011185340A

  • Glassfiber reinforced thermoplastic composition and molding thereof

    JP2015105359A

  • Polyphenylene sulfide resin composition and molded article formed from the same

    JP2017149797A